Health Informatics 3.0 and other Increasingly Dispersed Technologies Require Even Greater Trust: Promoting Safe Evidence-based Health Informatics - Rigby, M.; Ammenwerth, E.; Talmon, J.; Nykänen, P.; Brender, J.; de Keizer, N. (Yearbook of Medical Informatics, 2011)
Healthinformaticsisgenerallylesscommittedtoascientific evidence-basedapproach than any other area of health science, which is an unsound position. Introducing the new Web 3.0 paradigms into health IT applications can unleash a further great potential, able to integrate and distribute data from multiple sources. The counter sideisthatitmakestheuserandthepatientevermoredependentonthe‘blackbox’ of the system, and the re-use of the data remote from the author and initial context. Thus anticipatory consideration of uses, and proactive analysis of evidenceof effects,are imperative,as only when a clinical technology can be proven to be trustworthy and safe should it be implementedwidely as is the case with other health technologies.Toargueforpromotingevidence-basedhealthinformatics assystemsbecomemorepowerfulandpro-activeyetmoredispersed andremote;andevaluationasthemeansofgeneratingthenecessaryscientific evidencebase.TopresentongoingIMIAandEFMIinitiativesinthisfield.Critical overview of recent developments in health informatics evaluation, alongside the precedents of other health technologies, summarising current initiatives and the new challenges presented by Health Informatics 3.0.Web3.0should betaken asanopportunitytomovehealth informatics from being largely unaccountable to one of being an ethical andresponsiblescience-baseddomain.Recentandplannedactivities ofthe EFMIandIMIAworkinggroupshavesignificantlyprogressedkeyinitiatives.Concurrent with the emergence of Web 3.0 as a means of new-generation diffuse health information systems comes an increasing need for an evidence-based culture in health informatics.
Keywords: Health informatics; evaluation; Web 3.0; risk; business ethics